Effect of contrast injection into the biliary tract during intraoperative cholangiogram on postoperative liver function tests. Issue 2 (11th February 2015) - Wewelwala, Chandika; Cashin, Paul; Blamey, Stephen; Gribbin, John; Low, Liang; Croagh, Daniel
Abstract: Introduction: Postoperative abnormal liver function tests (LFT) following laparoscopic cholecystectomy (LC) could present a substantial clinical dilemma due to suspicion of missed choledocholithiasis or more serious complications such as bile duct injury. We noted that LFT were more likely to be abnormal when an intraoperative cholangiogram (IOC) had been performed. This study aims to examine if contrast injection into the biliary tract during IOC is associated with deranged LFT. Methods: Data on all LC performed in a tertiary referral hospital network over a period of 30 months were collected retrospectively, and two groups were identified depending on successful performance of an IOC. Identical inclusion and exclusion criteria were applied to both groups to identify eligible patients. Alkaline phosphatase, gamma‐glutamyl transferase (GGT), alanine transaminase (ALT), and bilirubin levels were recorded, and the mean difference between preoperative and postoperative values was analyzed. Results: There were 177 eligible patients: 147 patients in the LC with IOC test group (IOC group) and 30 patients in the LC without IOC control group (NO IOC group). Demographics and preoperative mean LFT were not significantly different between groups. In the IOC group, the mean ALT difference (43 ± 57, P =< 0.001) and GGT difference (34 ± 66, P =< 0.001) were significantly higher than in the NO IOC group (ALT [19 ± 25], GGT [7 ± 20]). The mean alkaline phosphatase difference (IOC [9 ± 47], NO IOC [−2 ± 14], P = 0.214) and mean bilirubin difference (IOC [−2 ± 9], NO IOC [−1 ± 8], P = 0.911) were not significantly different. Conclusion: The performance of an IOC is associated with elevated GGT and ALT but does not affect alkaline phosphatase and bilirubin concentrations.